2009
DOI: 10.4141/cjas08059
|View full text |Cite
|
Sign up to set email alerts
|

Short-term selection for yearling weight in a small-experimental Iranian Afshari sheep flock

Abstract: (1 , respectively. Estimates of heritabilities and observed genetic trends indicated that selective breeding can lead to significant genetic improvement in Afshari sheep. The average generation interval was estimated to be 3.35 yr. The shorter generation interval was observed on the sire side compared with the dam side (3.30 yr vs. 3.78 yr), indicating faster generation turnover for sires than for dams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Somewhat lower estimates have also been reported by Ekiz (2005) in Turkish Merino lambs (0.08) for ADG from weaning to 6 months of age and by Miraei-Ashtiani et al (2007) in Sangsari lambs (0.05) for ADG from weaning to 6 months of age. The lower estimates of h 2 in the present study for post-weaning daily gain compared to other studies might be due to unfavorable environmental conditions which lambs experience during the post-weaning period (Ghafouri-Kesbi et al 2009). It is well known that trait heritabilities are not constant but can vary with environmental conditions (Ghafouri-Kesbi et al 2009).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Somewhat lower estimates have also been reported by Ekiz (2005) in Turkish Merino lambs (0.08) for ADG from weaning to 6 months of age and by Miraei-Ashtiani et al (2007) in Sangsari lambs (0.05) for ADG from weaning to 6 months of age. The lower estimates of h 2 in the present study for post-weaning daily gain compared to other studies might be due to unfavorable environmental conditions which lambs experience during the post-weaning period (Ghafouri-Kesbi et al 2009). It is well known that trait heritabilities are not constant but can vary with environmental conditions (Ghafouri-Kesbi et al 2009).…”
Section: Discussionmentioning
confidence: 84%
“…The lower estimates of h 2 in the present study for post-weaning daily gain compared to other studies might be due to unfavorable environmental conditions which lambs experience during the post-weaning period (Ghafouri-Kesbi et al 2009). It is well known that trait heritabilities are not constant but can vary with environmental conditions (Ghafouri-Kesbi et al 2009). There are two alternate hypotheses that might explain this phenomenon.…”
Section: Discussionmentioning
confidence: 84%
“…The aim of the experiment was to evaluate the response of Afshari sheep to selection for yearling live weight (selection criterion). The location of the experimental flock, husbandry practices and the results of the selection program were described by Ghafouri-Kesbi et al (2009).…”
Section: Datamentioning
confidence: 99%
“…To do such an evaluation, I used breeding values of the first 10 influential ancestors for the selection criteria (yearling weight) to evaluate change in their ranking when their genetic contributions were replaced with their breeding values. Breeding values of individual animals were obtained with the best linear unbiased prediction (BLUP) method (Ghafouri-Kesbi et al 2009). …”
Section: Measures Of Genetic Diversitymentioning
confidence: 99%
“…The moderate pe 2 estimate for weaning weight indicates the importance of maternal permanent environment and maternal care during the period from birth to weaning, as lambs remained with their dams longer. Ghafouri-Kesbi et al (2009) reported that estimates of pe 2 are high at birth, when direct effects are the least important, but they decrease sharply after weaning and at the highest age this effect is negligible. However, Al-Shorepy et al (2002) found opposing results and related that although the permanent environmental effects had a higher influence on weaning weight than on birth weight, the genetic basis for these effects could not be interpreted.…”
Section: Genetic Parametersmentioning
confidence: 99%